Pengaruh Electronic Word Of Mouth Dan Persepsi Nilai Terhadap Minat Beli Pada Produk Uniqlo Di Surabaya - Panglima Revandityo Shije; Zumrotul Fitriyah (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The purpose of this research is to examine how the dependent variables of electronic word of mouth and perceived value influence the independent variable of intention to buy Uniqlo items. In order to get this information, inhabitants of the Surabaya region who are familiar with Uniqlo's goods participated in the survey. Purposive sampling was employed for this investigation, and the number of samples that were used was 110 respondents. Distribution of questionnaires serves as a method for collecting data, with the sample requirements being people of Surabaya who are familiar with Uniqlo goods, who are at least 17 years old, and who live in the city. This research makes use of a method known as partial least squares (PLS) for its analysis. The research that has been carried out has led to the discovery that the following statements are true: Electronic Word of Mouth has a favorable influence on purchase intention. There is a positive correlation between perceived value and the desire to make a purchase. It is advised that in order for Uniqlo to raise customer interest in purchasing their products, product differentiation should be more appealing than that of competing companies, and the quality that has been established should be maintained.